1990
DOI: 10.1159/000110749
|View full text |Cite
|
Sign up to set email alerts
|

Neurological Examination in Subjects over 65 Years: An Epidemiological Survey

Abstract: The frequency of abnormal findings at neurological examination was analyzed in an unselected sample of elderly people aged 67–87 years. Absent deep tendon reflexes and impairment of proprioceptive sensation rarely occurred in the elderly. Limitation of upward gaze and convergence appear a common finding, especially in the very old. Overall, the presence of cortical disinhibition signs (primitive reflexes and paratonia) did not discriminate well between subjects without CNS disease and demented patients. Only t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0
3

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 16 publications
4
19
0
3
Order By: Relevance
“…Os reflexos principais seriam o palmomentoniano, o de muxoxo e o de apreensão. Sua prevalência é muito variada entre os estudos: palmomentoniano (15,6%-36,4%), muxoxo (33%-73%) e apreensão (27%-67%) 34,35 . Diferentemente da criança, a presença de reflexos primitivos no idoso é considerada patológica e sua ocorrência é mais predominante na DA 34 .…”
Section: Retrogênese Neurológicaunclassified
See 1 more Smart Citation
“…Os reflexos principais seriam o palmomentoniano, o de muxoxo e o de apreensão. Sua prevalência é muito variada entre os estudos: palmomentoniano (15,6%-36,4%), muxoxo (33%-73%) e apreensão (27%-67%) 34,35 . Diferentemente da criança, a presença de reflexos primitivos no idoso é considerada patológica e sua ocorrência é mais predominante na DA 34 .…”
Section: Retrogênese Neurológicaunclassified
“…Diferentemente da criança, a presença de reflexos primitivos no idoso é considerada patológica e sua ocorrência é mais predominante na DA 34 . Nessa doença os reflexos de muxoxo e apreensão são os mais comuns 35 . O exame neurológico usualmente é considerado normal, exceto nas fases mais avançadas da doença, quando podem ser observados sinais extrapiramidais (rigidez, alterações posturais e da marcha), mioclonias e reflexos primitivos 22 .…”
Section: Retrogênese Neurológicaunclassified
“…Therefore, it is plausible to suggest that ISNAs may be an epiphenomenon of clinically covert brain vascular and/or degenerative damage. Past reports on these subtle neurological abnormalities have primarily focused on evaluating extrapyramidal features [16], while very few reports [17][18][19] have focused on those related to the dysfunction of other brain structures.…”
Section: Introductionmentioning
confidence: 99%
“…The activities of daily living (ADL) of the elderly are adversely affected by deterioration of motor, mental, and emotional functions. Such deterioration is often associated with chronic neurological disorders, such as cerebrovascular disease, Parkinson's disease and parkinsonism, dementia, and diseases of the spine or spinal cord, in addition to aging (2)(3)(4). Indeed, previous surveys found that the elderly residents in a community frequently had abnormal neurological symptoms and signs, and numerous symptomatic neurological disorders (2,3,5).…”
Section: Introductionmentioning
confidence: 99%
“…Such deterioration is often associated with chronic neurological disorders, such as cerebrovascular disease, Parkinson's disease and parkinsonism, dementia, and diseases of the spine or spinal cord, in addition to aging (2)(3)(4). Indeed, previous surveys found that the elderly residents in a community frequently had abnormal neurological symptoms and signs, and numerous symptomatic neurological disorders (2,3,5). Although most neuroepidemiological studies to date have been oriented towarddisease entities, a fewcommunitysurveys have been undertaken to define the prevalence of abnormal neurological manifestations and disability in ADLwithin a community (2,3,6,7).…”
Section: Introductionmentioning
confidence: 99%